Moral Kekeluargaan Dalam Film Anime "One Piece: Red" Karya Eiichiro Oda - Mayra Azzahra Larasati H; Arief Ruslan (KOMVERSAL, 2025)
This article examines the moral message of family in the anime film "One Piece: Red". The film "One Piece: Red" is a popular anime film released in 2022. This film also raises the theme of family and the relationships between members of a pirate crew. This research uses Roland Barthes semiotic analysis to examine the moral message of family in the film "One Piece: Red". Barthes semiotics views signs as systems of meaning that are structured and bound by certain rules. The aim of this research is to recognize and analyze the symbols and indicators contained in films that show family values. This film explores the fundamental meaning behind the images and narrative through Roland Barthes semiotic technique, which distinguishes between denotation and connotation. "One Piece: Red" continues to highlight the value of family members' support, sacrifice and unity. This film shows how family ties can be a source of strength in the face of adversity through the nuances of its characters and plot. This research adds to our knowledge of how popular anime can communicate important social and cultural values.